Peran Pos Bantuan Hukum ‘Aisyiyah Kalimantan Tengah terhadap Perlindungan Hukum Perempuan dan Anak Dimasa Pandemi Covid-19 - Sanawiah Sanawiah; Rita Rahmaniati (Anterior Jurnal, 2021)
This study aims to determine the role of ‘Aisyiyah's Legal Aid Post (Posbakum) Central Kalimantan in providing legal assistance and supporting the policies of the Palangka Raya city government towards legal protection for women and children amid the Covid-19 pandemic. A qualitative-descriptive approach that describes people's behavior by highlighting events in the field and certain activities in detail and depth was used as the research method. The study describes the role of Posbakum ‘Aisyiyah in the form of legal assistance activities for clients starting from the reporting to the court counseling by its lawyer. The cases handled are mostly domestic violence, inability to provide a living, and abandoning the wife and children for another woman. One of the successes of legal aid posts in handling cases of domestic violence is contained in a copy of decision number 473/Pdt.G/2020/PA.Plk. Meanwhile, Posbakum works with the Division of Women and Children’s Empowerment of the PPKBP3APM Office Palangka Raya City to provide counseling on family resilience and skill training for housewives to provide protection and empowerment for women and to improve the community economy amid the Covid-19 Pandemic